Free convection in wavy porous enclosures with non-uniform temperature boundary conditions filled with a nanofluid: Buongiorno’s mathematical model; Thermal Science; Vol. 21, iss. 3 - Sheremet M. A. Mikhail Aleksandrovich (2017, 2017)
Title screen